(3GdeLehYs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s ((3eMeO Hf CMeO Hf YeQ GdCfUGQi s)
(3ChdgG (B:s
(3HGH GdMjV bGd Gddg JYGdi hjSdhfc Yf GdeMjV bd gh CPi aGYJRdhG GdfSGA ai GdeMjV hdG JbQHhgf MJi jWgQf aEPG JWgQf aGJhgf ef MjK CeQce Gddg Ef Gddg jMH GdJhGHjf hjMH GdeJWgQjf (B" s
(3BNQgG (B:s
(3bGd GdHjgbi hdhUM dMed Ydi fGadI Jchf UMJgG eJhbaI Ydi UMI GdaQjVI hGddg CYde s
(3Ydjg GdYOjO ef GdJedcGJ ai Chdgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs